A lifetime of neurogenesis in the olfactory system - Brann, Jessica H.; Firestein, Stuart J. (Frontiers in Neuroscience, 2014)
Neurogenesis continues well beyond embryonic and early postnatal ages in three areas of the nervous system. The subgranular zone supplies new neurons to the dentate gyrus of the hippocampus. The subventricular zone supplies new interneurons to the olfactory bulb, and the olfactory neuroepithelia generates new excitatory sensory neurons that send their axons to the olfactory bulb. The latter two areas are of particular interest as they contribute new neurons to both ends of a first-level circuit governing olfactory perception. The vomeronasal organ and the main olfactory epithelium comprise the primary peripheral olfactory epithelia. These anatomically distinct areas share common features, as each exhibits extensive neurogenesis well beyond the juvenile phase of development. Here we will discuss the effect of age on the structural and functional significance of neurogenesis in the vomeronasal and olfactory epithelia, from juvenile to advanced adult ages, in several common model systems. We will next discuss how age affects the regenerative capacity of these neural stem cells in response to injury. Finally, we will consider the integration of newborn neurons into an existing circuit as it is modified by the age of the animal.